Insights from cardiopulmonary exercise testing in pediatric patients with hypertrophic cardiomyopathy. (14th October 2021) - Gallo, G; Mastromarino, V; Limongelli, G; Calcagni, G; Ragno, L; Valente, F; Musumeci, M B; Adorisio, R; Rubino, M; Autore, C; Magri', D
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is characterized by extremely varied phenotypic expression ranging from asymptomatic to heart failure (HF) to sudden cardiac death (SCD). Although children with HCM are considered in the highest risk spectrum, the most common recommendations on pharmacological and non-pharmacological treatment (i.e. drugs, ICD, septal reduction procedures, inclusion in cardiac transplantation list) are often disregarded or too much postponed in this setting and strong evidence-based risk prediction models are missing. A systematic cardiopulmonary exercise test (CPET) assessment might be helpful to disclose an unsuspected functional limitation. Purpose: The aim of our multicenter retrospective study was to investigate possible clinical insights, in terms of functional and prognostic assessment, coming from a full CPET assessment in a cohort of pediatric HCM outpatients aged less than 18 years old. Methods: Sixty consecutive pediatric HCM outpatients aged <18 years-old were enrolled, each of them undergoing a full clinical assessment including a CPET; a group of 60 healthy subjects served as controls. An unique composite end-point of HF-related and SCD or SCD-equivalent events was also explored. During a median follow-up of 53 months, a total of 13 HF- and 7 SCD-related first events were collected. Results: An impaired exercise capacity, consisting on peak VO2 values <80% of the predicted, has been found in the 78% of the study sample (n. 47 patients). Despite most of the HCM patients were classified in NYHA I functional class, most of them (n. 33, 73%) showed a reduced exercise capacity, the percentage of impaired exercise capacity raising in the NYHA II group (n. 14 patients, 93%). Respect to the control Group, the HCM patients showed a significantly poorer functional status in terms of maximum workload achieved, peak VO2 (regardless the adopted correction), circulatory power and VE/VCO2 slope values (Figure 1, panel A). HCM patients who experience adverse events during the follow-up (Event Group) showed the worst CPET profile (Figure 1, panel B). The composite end-point occurred more frequently in patients with the worst CPETs' profiles. At the univariate analysis, peak VO2% was the variable with the strongest association with adverse events at follow-up (C-index=0.72, p=0.025) and a cut-off value equal to 60% was the most accurate in identifying those patients at the highest risk (Figure 2). Conclusions: Our findings support the role of CPET analysis as an insightful approach in the young HCM clinical management. In a group of young asymptomatic or slightly symptomatic HCM patients, the CPET allowed us to estimate accurately their functional capacity and to disclose a portion of un-recognized exercise impairment. Our data argue in favor of a possible role of some CPET-derived variables in the early identification of those young HCM patients at highest risk of HCM related events. Funding Acknowledgement: Type of funding sources: None.